Korelasi antara Minat Belajar dengan Hasil Belajar Siswa pada Mata Pelajaran Fikih di MI DDI Batubessi Kabupaten Barru - Hartini Sultan; Amaluddin Amaluddin; St. Wardah Hanafie Das (JURNAL EDUKASI NONFORMAL, 2022)
This study aims to provide an overview of student interest in learning and student learning outcomes at MI DDI Batubessi and the correlation between interest in learning and student learning outcomes at MI DDI Batubessi. The method used in this study is a quantitative method, several methods for collecting data are observation, questionnaires and documentation. This research was conducted in MI DDI Batubessi, Barru district. The results of the study show: 1). Students' learning interest in fiqh subjects at MI DDI Batubessi is 1317 with an average score of 23.5. 2). Student learning outcomes in fiqh subjects at MI DDI Batubessi seen from report cards are 4520 with an average value of 82.18. 3). For the correlation between interest in learning and student learning outcomes in fiqh subjects at MI DDI Batubessi using the product moment correlation formula which shows a significant correlation with student achievement in fiqh subjects.